2011
DOI: 10.2174/157016111793744661
|View full text |Cite
|
Sign up to set email alerts
|

Low Molecular Weight Heparin: Current Evidence for Its Application in Orthopaedic Surgery

Abstract: Low molecular weight heparin (LMWH) is used in orthopaedic surgery largely for prophylaxis of venous thromboembolism (VTE). The purpose of this study was to review the available evidence to better define its role. The most recent American College of Chest Physicians Evidence-Based Practice guidelines for the most current recommendations for the application of LMWH to orthopaedic surgery are reviewed. A systematic review of the literature was undertaken using MEDLINE database and manual searches, the terms low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Enoxaparin is the LMWH that is commonly used for both VTE prophylaxis and treatment. Enoxaparin has the largest body of clinical evidence supporting its use across the spectrum of VTE management and has been used as the reference standard comparator anticoagulant in trials of new anti-coagulants Bharathi Kalyani et al [16] conducted a systematic review of literature using Medline database and showed that Enoxaparin was found to be more cost effective in orthopedic surgeries. [17] .…”
Section: Resultsmentioning
confidence: 99%
“…Enoxaparin is the LMWH that is commonly used for both VTE prophylaxis and treatment. Enoxaparin has the largest body of clinical evidence supporting its use across the spectrum of VTE management and has been used as the reference standard comparator anticoagulant in trials of new anti-coagulants Bharathi Kalyani et al [16] conducted a systematic review of literature using Medline database and showed that Enoxaparin was found to be more cost effective in orthopedic surgeries. [17] .…”
Section: Resultsmentioning
confidence: 99%
“…In another study, even a reduction of MMP-9 concentration and activity has been reported in the plasma of LMWH-treated patients with abdominal aortic aneurysm [57], an effect which might be connected to the LMWH-dependent downregulation of IL-8 as shown in enoxaparin-treated epithelial cells [48]. Accordingly, LMWH is increasingly used as an anticoagulant, e.g., for VTE prevention [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…In this patient group, up to 40-60% of the patients have asymptomatic, objectively confirmed DVT (38). Research during the past ten years has shown that prophylactic treatment with low molecular weight heparin (LMWH) can reduce the incidence of postoperative VTE (38,39). Patients undergoing general surgery such as abdominal, urological, gynaecological surgery have about 20 % risk of VTE whereas the same kind of surgery in cancer patients is associated with a risk of almost 40%.…”
Section: Surgery and Plaster Cast Treatmentmentioning
confidence: 99%